(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the effect of the facial type on the perceptions of varying degrees of deviation from the midline by laypeople. The face image of two mesofacial individuals (male and female) was manipulated in the photoshop program in order to produce the other two facial types (brachyfacial and dolichofacial), as well as in each image, midline deviations (1.0 to 4.0 mm). The photographs were taken with a canon xti camera, with a macro lens, obeying the same distance for both participants, with natural head position. The images generated were evaluated by laypeople, who constituted the universe of the sample. The sample corresponded to 150 participants selected for convenience, using the non-probabilistic sampling technique. The evaluators rated the attraction and acceptance of each photograph. The collected data were tabulated in spreadsheets in the Excel program and evaluated in the Statistica for Windows 7.0 program, with a significance level of 5%. It is observed that the facial type is influenced by the degree of perception of the midline deviation and is influenced by sex and age. The facial type that is most influenced is dolichocephalic and the least affected is brachycephalic. The deviation from the midline in the upper arch was noticeable by laypeople, however a deviation of up to 2 mm from the midline in orthodontic treatment would be acceptable.